Herbal Decoction Divya-Peedantak-Kwath Alleviates Allodynia and Hyperalgesia in Mice Model of Chemotherapy-Induced Peripheral Neuropathy via Modulation in Cytokine Response - Balkrishna, Acharya; Sakat, Sachin S.; Karumuri, Shadrak; Singh, Hoshiyar; Tomer, Meenu; Kumar, Ajay; Sharma, Niti; Nain, Pradeep; Haldar, Swati; Varshney, Anurag (Frontiers in Pharmacology, 2020)
The widely used cancer treatment, chemotherapy, causes severe long-term neuropathic pain in 30-40 % cases; the condition clinically known as chemotherapy induced peripheral neuropathy (CIPN). Approved conventional analgesics are sometimes ineffective while others like opioids have undesirable side effects like, addiction, seizures and respiratory malfunctioning. Tricyclic anti-depressants and anticonvulsants, though exhibit anti-allodynic effects in neuropathy, also have unpleasant side-effects. Thus, alternative medicines are being explored for CIPN treatment Despite scattered reports on different extracts from different plants having potential anti-allodynic effects against CIPN, no established medicine or formulation of herbal origin exists. In this study, efficacy of an herbal decoction, formulated based on ancient medicinal principles and protocols for treating neuropathic pain, Divya-Peedantak-Kwath (DPK), has been evaluated in paclitaxel (PTX) induced peripheral neuropathic mouse model. We observed that, DPK has prominent anti-allodynic and anti-hyperalgesic effects and acts as a nociceptive modulator for CIPN. With exhibited anti-oxidative effects, DPK restored the redox potential of the sciatic nerves to the normal. On histopathological evaluation, DPK reversed the PTX induced lesions in the sciatic nerve, in a dose dependent manner. It also prevented inflammation by modulating the levels of pro-inflammatory cytokines involved in CIPN pathogenesis. Our observations evinced that DPK can alleviate CIPN by attenuating oxidative stress and concomitant neuroinflammation through immune modulation.